Energy shocks and detecting influential industries. (15th April 2017) - Kang, Dongsuk; Lee, Duk Hee
Abstract: An industry's relationship of supply and demand with the energy sector can be a critical factor in the stability of its economic performance. Furthermore, the patterns of industry dependence on energy industries can be a major characteristic of entire industrial structure. This research evaluates industries' impact scores for their overall influence on other industries and vulnerability to supply and demand shocks from the energy sector. The study utilizes a sample of Korea's industrial input–output tables from 2010 to 2012. Using a chain of complementary methodologies, this study finds that among four clusters, energy, services, and raw materials are key members that can spread energy shocks to other industries. Therefore, governments need to prepare effective energy efficiency policies for these target industries. Highlights: We analyze an industry's impact score of its vulnerability to energy shock and inter-industrial effects. We utilize the sample of input-output tables in Korea from 2010 to 2012. We implement simulation, PCA, TOPSIS, cluster analysis about energy shock and industrial trades. Subsectors of energy, services, raw material are subject to energy shock and influential to others. These bridge industries can be targets that require policies for effective energy efficiency.